Silver nanoparticles coated with dodecanethiol used as fillers in non-cytotoxic and antifungal PBAT surface based on nanocomposites - Ferreira, F. V. (2019)
In the present study, we report the preparation of antifungal and non-cytotoxic polymer nanocomposites with potential application in biomedical materials. Dodecanethiol-protected silver nanoparticles (AgNPs-DDT) were synthesized by a reduction/precipitation method and dispersed in chloroform to obtain stable colloidal dispersions. PBAT-based nanocomposites containing 0.25, 0.5 and 2 wt% AgNPs-DDT were prepared by casting method. The incorporation of AgNPs-DDT in PBAT matrix resulted in nanocomposites which combine improved mechanical performance and antifungal properties with a non-cytotoxic characteristic.